Study on the Photodegradation of Nanocomposites Based on Polypropylene and tio2 Nanotubes - Rabagliati-Canessa, F; Sepulveda-Palma, F; Zapata-Ramirez, P (Elsevier Ltd, 2016)
Composites of polypropylene (PP) were synthesized by the melting process in the presence of titanium dioxide nanotubes (TiO2-Ntbs). Nanotubes were used either as synthesized or organically modified with hexadecyltrimethoxysilane (Mod-TiO2-Ntbs). The photoageing of the neat PP and PP-TiO2-Ntbs was studied during 10 days. The nanotubes incorporated into the PP promoted and accelerated its photodegradation due to reactive species generated during irradiation. PP-Mod-TiO2-Ntbs composites with 8% of modified nanotubes produced the highest degradation according to chemiluminescence analysis (CL), carbonyl index (CI), degree of crystallinity (%χ), and thermogravimetric analysis (TGA). Furthermore, SEM analysis after photoageing the polymers presented several cavities of ca. 5 μm. © 2016 Elsevier Ltd